Ibsen, Bjørnson and the art of acting - Hyldig, Keld (Nordlit, 2015)
In this article Henrik Ibsen’s and Bjørnstjerne Bjørnson’s contribution to the development of acting in Norwegian theatre are discussed within the background of Danish romantic acting. In the 1850s and -60s both were active as theatre critics, directors and dramatists. Both had a view on theatre and acting marked by a mixture of romantic and realistic ideas, and both urged for the development of Norwegian acting in continuation of Danish and European traditions. It was, however, Bjørnson, who to begin with, came to be most influential with regard to what direction the acting style, among the Norwegian actors, developed. Through his inspiration and efforts a specific national coloured way of acting developed and came to dominate Norwegian theatre at least until the beginning of the 20th century. The influence from Ibsen – and the development of a Norwegian Ibsen tradition – has first of all come from his contemporary plays. A specific Ibsenian (i.e. psychological realistic) acting style developed gradually from the 1880s and onwards, through the actors’ work with the characters in Ibsen’s contemporary plays.